"You're damned if you do, you're damned if you don't": a qualitative exploration of parent motives for provision of mobile screen devices in early childhood - Sumudu R. Mallawaarachchi; Merrilyn Hooley; Wendy Sutherland-Smith; Sharon Horwood (BMC, 2022)
Abstract Background Exploring parental motives for providing smartphones and tablets to young children is important to better understand ways to optimise healthy use of mobile screens in early childhood. To date, no study has qualitatively examined the factors underpinning parental motives of providing mobile screens to young children, using a theoretically driven approach. Methods We conducted 45 in-depth, semi structured online interviews with primary caregivers of toddlers and pre-schoolers from diverse family backgrounds who participated in a large online survey in Australia. Themes were generated from the transcribed interviews using template thematic analysis. The coding was completed deductively using the Theory of Planned Behaviour (TPB) and data-driven induction. Results Participants consistently reported a spectrum of attitudes, subjective norms and perceived behavioural control aspects which drove their decision to provide or not provide a mobile screen device to their child. Five main descriptive themes were generated, guided by the TPB: (1) Convenience, connection, and non-traditional learning experience; (2) Negative behavioural consequences and potential activity displacement through mobile screens; (3) Influences of society and resources; (4) Managing and achieving a balance; (5) External challenges. Conclusions Overall, the findings demonstrated that parents experienced cognitive dissonance between their attitudes and behaviour, primarily from perceived behavioural control and subjective norms negating the influence of attitudes on their motives to provide a device. These insights offer important avenues for public health messaging and resources to better involve and support parents in decision-making relating to mobile screens in everyday lives of young children.